476. Comparison of Community-Associated Clostridium difficile Infections With Other Reportable Enteric Pathogens, Minnesota, 2016. (26th November 2018) - Balius, Patrick; Bye, Maria; Smith, Kirk; Holzbauer, Stacy
Abstract: Background: Differentiating community-associated (CA) Clostridium difficile infections (CDI) from acute diarrhea due to other etiologies among patients with no antibiotic exposure is difficult. MDH performs active population- and laboratory-based surveillance for CDI, other bacterial diarrheal illnesses (BDI) ( Campylobacter, enteric E. coli, Salmonella, Shigella, Vibrio, Yersinia ), and parasitic diarrheal illness (PDI) (Amebiasis, Cryptosporidium, Giardia ). We compared characteristics of patients with CA-CDI vs. other etiologies reported to the Minnesota Department of Health (MDH) from Benton, Morrison, Olmsted, Stearns and Todd counties in 2016. Methods: CA-CDI cases were defined as a positive molecular assay, culture, or toxin, on a stool specimen from a person >1 year old without an overnight hospital/long-term care facility stay in the prior 12 weeks living in one of five Minnesota counties. Reported BDI and PDI cases >1 year old from the same counties were compared with CDI cases. Standardized interviews were attempted. Polytomous regression was used to detect differences in demographics and clinical presentation. Results: During 2016, 1, 064 reportable diarrheal illnesses were reported (525 CA-CDI cases [129 per 100, 000 population], 341 BDI cases [84 per 100, 000], and 198 PDI cases [49 per 100, 000]); 66% of CA-CDI, 89% of BDI and 59% of PDI were interviewed. CDI cases were less likely to be 1–17 years compared with BDI or PDI cases (PDI OR: 0.07 [0.05, 0.1]; BDI OR: 0.3 [0.2, 0.4]) and more likely to be 65+ age years (PDI OR: 12.2 [5.3, 27.8]; BDI OR: 2.3[1.6, 3.3]). CDI cases were more likely to be female (PDI OR: 2.0 [1.4, 2.8]; BDI OR: 1.6 [1.3, 2.3]). CDI cases had higher median days of diarrhea before seeking care (CDI = 8 days vs. PDI = 7 days, P < 0.02; vs. BDI = 4 days, P < 0.001), longer duration of diarrhea (CDI = 14 days vs. PDI = 13 days, [ P = 0.02]; vs. BDI = 7 days, P < 0.001), and were less likely to report emesis (PDI OR: 0.3 [0.2, 0.4], BDI OR: 0.5 [0.3, 0.7]). CDI cases were less likely to report fever than BDI cases (OR: 0.3[0.2, 0.4]). Conclusion: CA-CDIs in Minnesota are as common as all other reportable enteric pathogens combined. We identified differences in age, gender, and clinical presentation that may help guide clinical testing and initial treatment, especially in healthy adults. Disclosures: All authors: No reported disclosures.